Developing Undergraduate Management Students ‘Reflection Capabilities' - Jenert, Tobias; Wagner, Dietrich; Gommers, Luci; Brahm, Taiga (Academy of Management Proceedings)
Business schools have been repeatedly confronted with demands to change their ways of educating future managers. Much of the current criticism focuses on content-related aspects of management education, targeting economic theory and management studies as an academic discipline. However, addressing what is taught alone has a very limited scope. Business schools also need to equip their students and their instructors with capabilities that allow them to question the viability of the theories, models and concepts for solving specific management tasks. In other words: Managers and therefore management education need to become more reflective in their practices. We present a study addressing the following research questions (1) What is the current level of reflective capabilities in management students across different business schools/programmes and in comparison to students in other disciplines? (2) Which characteristics of educational contexts influence the development of reflective capabilities? (3) What kinds of interventions for developing student reflection are suitable for being implemented in typical large-cohort undergraduate management programmes? Therefore we developed a survey measuring both students’ reflection modes (dependent variables) as well as factors influencing these modes (independent variables). We measured student reflection at two universities with a total sample of 747 students. Results show that undergraduate management students reflect less on their studies than their counterparts in other subjects. Second, we found that undergraduate management education seems to worsen than to improve students’ readiness to reflect. We used our findings to systematize existing teaching and learning methods and suggest a basic structure for effective interventions to foster undergraduate management students’ reflection capabilities.